Stories untold : the street children of Chow Kit – an architectural intervention / Anniz Fazli Ibrahim Bajunid, Mohamad Yusuf Aliaas and Ramli Abdullah - Aliaas, Mohamad Yusuf; Abdullah, Ramli (Faculty of Architecture, Planning and Surveying, 2012)
Chow Kit Road, a busy shopping sanctuary flourishes with economic activities with more than 500 ‘street children’ roaming and living off the streets. These children have been ignored, and much of their life challenges remain unaddressed. This conceptual paper initiates an educational discussion in relation to their environment with a speci